Pyrone hydroperoxide formation during the Maillard reaction and its implication in biological systems - Lertsiri, Sittiwat; Fujimoto, Kenshiro; Miyazawa, Teruo (Biochimica et biophysica acta, 1995)
Hydroperoxide formation during Maillard reaction (amino-carbonyl reaction) was investigated using luminol-chemiluminescence-high performance liquid chromatography (CL-HPLC). From the equimolar reaction mixture of I M β-alanine/ d-glucose in phosphate buffer (pH 8.0) at 95°C, two hydroperoxides and H 2O 2 were detected as chemiluminescent products in CL-HPLC, and the yields were proportional to the browning development. One of these hydroperoxides was isolated and identified as 3-hydroxy-5-hydroperoxy-2-methyl-5,6-dihydropyran-4-one (HMDP, pyrone hydroperoxide) by fast atom bombardment mass spectrometry. The HMDP formation was also confirmed in l-lysine/ d-glucose and in bovine serum albimin/ d-glucose with the physiological incubation at 37°C for 4 days and 3 wk, respectively. Incubation at 37°C of human plasma containing 5.5–25.0 mM of d-glucose for 60 h showed th glucose concentration-dependent formation of HMDP (10–35μM of H 2O 2 equivalence). The HMDP was negative to thiobarbituric acid reaction and was degraded by peroxidases such as horseradish peroxidase, Athromyces ramosus peroxidase, heated cytochrome c, and microperoxidase. The results strongly suggested the formation of such hydroperoxide even in biological Maillard reaction termed as glycation, and implied its contribution in pathogenesis and oxidative lesions associated with hyperglycemia.